An economic evaluation of the impact of widespread antiretroviral treatment on secondary hospital in South Africa : case study of the GF Jooste Hospital Antiretroviral Referral Unit - Kevany, Sebastian (Health Economics Unit, 2014)
Includes bibliographical references.